Assessment of Heterosis in Inter-varietal Hybrids of Mangalore Melon (Cucumismelo var. acidulus) for Yield and Quality Traits - Shet, Ratnakar M.; Shantappa, T.; Satish, D.; Kumbar, Shivadatta (International Journal of Economic Plants, 2024)
Mangalore melon is one of the distinct class of Cucurbitaceae family widely grown in southern part of India. Despite of having many nutritional values, there is scope for systematic hybridization study to improve the many qualitative and quantitative traits. An investigation was undertaken to develop inter-varietal hybrids and their evaluation to assess the extent of heterosis in newly developed hybrids between selected genotypes of Mangalore melon during kharif, 2019 and 2020 at College of Horticulture, Sirsi, Karnataka, India. A total of 16 intervarietal hybrids were developed by crossing 15 parental lines. Hybrids were developed using hand emasculation and hand pollination technique and the developed hybrids were evaluated using RCBD design with two replications. The results showed significant positive heterosis over mid parent and better parent for all the hybrids. The hybrids Soubhagya×RNMS-1 exhibited highest and significant heterosis over both mid parent (88.05%) and better parent (72.69%) followed by MS-19×MS-5 over mid parent (73.09%) and better parent (61.10%). From this study, it was concluded that hybrid Soubhagya X RNMS-1 was superior over their parents for most of the traits with the total yield of 8.44 kg plant-1. These best performing hybrids are need to be studied for their stability and commercial exploitation, resistance of pest and diseases, keeping quality of hybrids (storability) and experimentation on hybrid seed production technologies as well as storability of seeds should be done.